Clinical, genomic, and pharmacological study of MYCN-amplified RB1 wild-type metastatic retinoblastoma - Zugbi, Santiago (2020)
An uncommon subgroup of unilateral retinoblastomas with highly aggressive histological features, lacking aberrations in RB1 gene with high-level amplification of MYCN (MCYNampl RB1+/+) has only been described as intra-ocular cases treated with initial enucleation. Here, we present a comprehensive clinical, genomic, and pharmacological analysis of two cases of MCYNampl RB1+/+ with orbital and cervical lymph node involvement, but no central nervous system spread, rapidly progressing to fatal disease due to chemoresistance. Both patients showed in common MYCN high amplification and chromosome 16q and 17p loss. A somatic mutation in TP53, in homozygosis by LOH, and high chromosomal instability leading to aneuploidy was identified in the primary ocular tumor and sites of dissemination of one patient. High-throughput pharmacological screening was performed in a primary cell line derived from the lymph node dissemination of one case. This cell line showed resistance to broad spectrum chemotherapy consistent with the patient’s poor response but sensitivity to the synergistic effects of panobinostat–bortezomib and carboplatin–panobinostat associations. From these cells we established a cell line derived xenograft model that closely recapitulated the tumor dissemination pattern of the patient and served to evaluate whether triple chemotherapy significantly prolonged survival of the animals. We report novel genomic alterations in two cases of metastatic MCYNampl RB1+/+ that may be associated with chemotherapy resistance and in vitro/in vivo models that serve as basis for tailoring therapy in these cases.